2022
DOI: 10.3390/insects13121076
|View full text |Cite
|
Sign up to set email alerts
|

Mosquitoes and Mosquito-Borne Diseases in Vietnam

Abstract: Mosquito-borne diseases pose a significant threat to humans in almost every part of the world. Key factors such as global warming, climatic conditions, rapid urbanisation, frequent human relocation, and widespread deforestation significantly increase the number of mosquitoes and mosquito-borne diseases in Vietnam, and elsewhere around the world. In southeast Asia, and notably in Vietnam, national mosquito control programmes contribute to reducing the risk of mosquito-borne disease transmission, however, malari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 132 publications
0
1
0
Order By: Relevance
“…This is consistent with another study conducted in September and October 2018 in the same area around Hanoi, which also found that there were fewer mosquitoes in urban areas than in peri-urban areas 21 . This could be due to higher awareness in urbanized settings, leading to better implementation of mosquito control, or less availability of breeding sites and blood-meal hosts 3 . Additionally, we found that the average monthly temperatures in the urban area were higher and the average monthly humidity was lower when compared to both the suburban and peri-urban areas.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is consistent with another study conducted in September and October 2018 in the same area around Hanoi, which also found that there were fewer mosquitoes in urban areas than in peri-urban areas 21 . This could be due to higher awareness in urbanized settings, leading to better implementation of mosquito control, or less availability of breeding sites and blood-meal hosts 3 . Additionally, we found that the average monthly temperatures in the urban area were higher and the average monthly humidity was lower when compared to both the suburban and peri-urban areas.…”
Section: Discussionmentioning
confidence: 99%
“…Vector-borne viruses collectively account for close to 700,000 deaths each year and are rapidly emerging as prominent threats to local populations 1 , 2 . Factors that may change vector dynamics and can alter vector abundance, such as urbanization, changes in land-use, deforestation, and climate change contribute to the escalating prevalence of mosquito-borne illness worldwide 3 .Understandng the abundance and dynamics of mosquito vectors is crucial for assessing the risks of arboviral diseases and anticipating future outbreaks 4 6 , and to enable timely implementation of control measures to mitigate the risk of human infection 4 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are over three thousand species of mosquitoes known worldwide, a few of them capable of transmitting diseases to humans. The major MBDs are malaria, dengue (DENV), Zika (ZIKV), chikungunya (CHIKV), Japanese encephalitis, yellow fever (YFV), filariasis, West Nile Virus (WNV) and Rift Valley Fever (Huynh et al, 2022). Some of these diseases can cause severe clinical conditions and even death.…”
Section: Mosquito-borne Diseasesmentioning
confidence: 99%
“…minimus, Aedes spp, and An. Epiroticus mainly transmits these diseases in urban and adjoining regions in the Southeast of Ho Chi Minh City and Binh Duong Province [3].…”
Section: Introductionmentioning
confidence: 99%